Prolyl hydroxylase domain 2 reduction enhances skeletal muscle tissue regeneration after soft tissue trauma in mice. - Stephan Settelmeier; Timm Schreiber; Joni Mäki; Nadiya Byts; Peppi Koivunen; Johanna Myllyharju; Joachim Fandrey; Sandra Winning (PLoS ONE, 2020)
The transcription factor Hypoxia-inducible factor 1 (HIF-1) plays a pivotal role in tissue regeneration. HIF-1 is negatively controlled by O2-dependent prolyl hydroxylases with a predominant role of prolyl hydroxylase 2 isoform (Phd2). Transgenic mice, hypomorphic for this isoform, accumulate more HIF-1 under normoxic conditions. Using these mice, we investigated the influence of Phd2 and HIF-1 on the regenerative capability of skeletal muscle tissue after myotrauma. Phd2-hypomorphic and wild type mice (on C57Bl/6 background) were grouped with regeneration times from 6 to 168 hours after closed mechanic muscle trauma to the hind limb. Tissue samples were analysed by immuno-staining and real-time PCR. Bone marrow derived macrophages of wild type and Phd2-hypomorphic mice were isolated and analysed via flow cytometry and quantitative real-time PCR. Phd2 reduction led to a higher regenerative capability due to enhanced activation of myogenic factors accompanied by induction of genes responsible for glucose and lactate metabolism in Phd2-hypomorphic mice. Macrophage infiltration into the trauma areas in hypomorphic mice started earlier and was more pronounced compared to wild type mice. Phd2-hypomorphic mice also showed higher numbers of macrophages in areas with sustained trauma 72 hours after myotrauma application. In conclusion, we postulate that the HIF-1 pathway is activated secondary to a Phd2 reduction which may lead to i) higher activation of myogenic factors, ii) increased number of positive stem cell proliferation markers, and iii) accelerated macrophage recruitment to areas of trauma, resulting in faster muscle tissue regeneration after myotrauma. With the current development of prolyl hydroxylase domain inhibitors, our findings point towards a potential clinical benefit after myotrauma.